Using magnetic resonance relaxometry to evaluate the safety and quality of induced pluripotent stem cell-derived spinal cord progenitor cells - Tan, Jerome (2025)
Background: The emergence of induced pluripotent stem cells (iPSCs) offers a promising approach for replacing damaged neurons and glial cells, particularly in spinal cord injuries (SCI). Despite its merits, iPSC differentiation into spinal cord progenitor cells (SCPCs) is variable, necessitating reliable assessment of differentiation and validation of cell quality and safety. Phenotyping is often performed via label-based methods including immunofluorescent staining or flow cytometry analysis. These approaches are often expensive, laborious, time-consuming, destructive, and severely limits their use in large scale cell therapy manufacturing settings. On the other hand, cellular biophysical properties have demonstrated a strong correlation to cell state, quality and functionality and can be measured with ingenious label-free technologies in a rapid and non-destructive manner. Method: In this study, we report the use of Magnetic Resonance Relaxometry (MRR), a rapid and label-free method that indicates iron levels based on its readout (T2). Briefly, we differentiated human iPSCs into SCPCs and compared key iPSC and SCPC cellular markers to their intracellular iron content (Fe3+) at different stages of the differentiation process. Results: With MRR, we found that intracellular iron of iPSCs and SCPCs were distinctively different allowing us to accurately reflect varying levels of residual undifferentiated iPSCs (i.e., OCT4+ cells) in any given population of SCPCs. MRR was also able to predict Day 10 SCPC OCT4 levels from Day 1 undifferentiated iPSC T2 values and identified poorly differentiated SCPCs with lower T2, indicative of lower neural progenitor (SOX1) and stem cell (Nestin) marker expression levels. Lastly, MRR was able to provide predictive indications for the extent of differentiation to Day 28 spinal cord motor neurons (ISL-1/SMI-32) based on the T2 values of Day 10 SCPCs. Conclusion: MRR measurements of iPSCs and SCPCs has clearly indicated its capabilities to identify and quantify key phenotypes of iPSCs and SCPCs for end-point validation of safety and quality parameters. Thus, our technology provides a rapid label-free method to determine critical quality attributes in iPSC-derived progenies and is ideally suited as a quality control tool in cell therapy manufacturing.